Drainage networks, lakes and water fluxes beneath the Antarctic ice sheet. Issue 72 (4th July 2016) - Willis, Ian C.; Pope, Ed L.; Leysinger Vieli, Gwendolyn J.-M.C.; Arnold, Neil S.; Long, Sylvan
ABSTRACT: Antarctica Bedmap2 datasets are used to calculate subglacial hydraulic potential and the area, depth and volume of hydraulic potential sinks. There are over 32 000 contiguous sinks, which can be thought of as predicted lakes. Patterns of subglacial melt are modelled with a balanced ice flux flow model, and water fluxes are cumulated along predicted flow pathways to quantify steady-state fluxes from the main basin outlets and from known subglacial lakes. The total flux from the continent is 21 km 3 a −1 . Byrd Glacier has the greatest basin flux of 2.7 km 3 a −1 . Fluxes from subglacial lakes range from 1 × 10 −4 to 1.5 km 3 a −1 . Lake turnover times are calculated from their volumes and fluxes, and have median values of 100 a for known 'active' lakes and 500 a for other lakes. Recurrence intervals of a 0.25 km 3 flood range from 2 months to 2000 a (median ≈130 a) for known 'active' lakes and from 2 to 2400 a (median ≈ 360 a) for other lakes. Thus, several lakes that have recently been observed to fill and drain may not do so again for many centuries; and several lakes that have not, so far, been observed to fill and drain have the potential to do so, even at annual to decadal timescales.